2018
DOI: 10.1111/pai.12855
|View full text |Cite
|
Sign up to set email alerts
|

Does asthma affect school performance in adolescents? Results from the Swedish population‐based birth cohort BAMSE

Abstract: Our results indicate that asthma impairs school performance in adolescence. Moreover, some evidence suggests the adolescents with asthma during school age and with poorer asthma control to be more likely to perform less well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Several studies have found a negative association between asthma and academic performance, while others have found none . This could be because of the heterogeneity of asthma and that most cases are mild and controlled which may not influence learning and cognition, where as other phenotypes of asthma such as uncontrolled, severe or late onset asthma may have a more obvious impact on learning and performance . Another reason for a lack of consistency between study findings could be due to heterogeneity of the confounding factors adjusted for and the impact of possible unmeasured confounding.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have found a negative association between asthma and academic performance, while others have found none . This could be because of the heterogeneity of asthma and that most cases are mild and controlled which may not influence learning and cognition, where as other phenotypes of asthma such as uncontrolled, severe or late onset asthma may have a more obvious impact on learning and performance . Another reason for a lack of consistency between study findings could be due to heterogeneity of the confounding factors adjusted for and the impact of possible unmeasured confounding.…”
Section: Introductionmentioning
confidence: 98%
“…Although asthma has been shown to be associated with increased absenteeism and in turn absenteeism has been shown to be associated with reduced academic performance, the direct association between asthma and academic performance is unclear. Several studies have found a negative association between asthma and academic performance, while others have found none . This could be because of the heterogeneity of asthma and that most cases are mild and controlled which may not influence learning and cognition, where as other phenotypes of asthma such as uncontrolled, severe or late onset asthma may have a more obvious impact on learning and performance .…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish population-based birth cohort study (BAMSE) investigated how asthma affects school performance in adolescents. 124 Multimorbidity and poor asthma control increased the likelihood of poorer school performance. Allergic rhinitis lowers the QoL and can lead to loss of productivity in the workplace.…”
Section: So CI O -Economi C Impac Tmentioning
confidence: 99%
“…This issue contains several articles related to asthma and allergic airway diseases, including one analyzing factors influencing variation of spirometric indices and fractional exhaled nitric oxide level (FeNO) in relation to their genetic and environmental determinants . In addition to this, you will find an article on results from a large birth cohort from Taiwan in which food allergy during early life, lower respiratory tract infection, and longer durations of symptomatic AD were found to influence later asthma development; as well as another on children from the Swedish BAMSE birth cohort who were shown to have poorer school performances if their asthma was uncontrolled …”
mentioning
confidence: 99%
“…BAMSE birth cohort who were shown to have poorer school performances if their asthma was uncontrolled. 3 I would like to focus on education, specifically education in asthma control. In this issue, Guarnaccia et al 4 report on over 800 pre-adolescents and adolescents who benefited from a diagnostic therapeutic educational pathway (DTEP) on asthma control.…”
mentioning
confidence: 99%